PENGARUH DIVERSITAS DEWAN KOMISARIS DAN DIREKSI PADA NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013 - Dewi, Gde Krisna; Dewi, Ayu Arysta (E-Jurnal Akuntansi, 2016)
This research is purposed to examine the effect of board of commissioner and director diversity to firm value. This research using finance companies listed in Indonesia Stock Exchange in period 2004-2009 as a research sample. The result obtained by purposive sampling is 33 companies which are fit with the sample criteria. The hypothesis tested by using multiple regression analysis.The result of hypothesis testing shows that presence of women on the board (gender diversity), and variation of formal education background (education diversity) influence to firm value. The result also shows that proportion of outside director (board’s independence) has no effect to firm value. Firm size as a control variable is also has no effect to firm value.
Keywords: board diversity, firm value, corporate governance, board commissioner, board of director.